Influence of Employee Engagement on Job Satisfaction of Library Staff in Public Tertiary Institutions in Ogun and Oyo States - Ajibare, Oluwaseun O.; Okegade, Motunrayo S. (Communicate: Journal of Library and Information Science, 2025)
For decades, job satisfaction significantly impacts organizational success. It plays important roles in determining an organization's productivity. This study investigated the influence of employee engagement on job satisfaction of library staff in public tertiary institutions in Ogun and Oyo States, Nigeria. Seven institutions (Tai Solarin University of Education Ijegun, Ijebu Ode; Institute of Technology, Igbesa; Federal College of Education, Osiele; Federal Polytechnic Ilaro; Gate Way Polytechnic Saapade and Moshood Abiola Polytechnic, Abeokuta, Ogun state, and The Polytechnic Ibadan, Oyo were studied. Descriptive research was used to analyze the data collected from the population of library staff selected from the study area. A total enumeration sampling technique was adopted making 138 library staff as the sample size. The descriptive and inferential statistics employed in the data analysis revealed that the dependability coefficients for each variable ranged between 0.710 and 0.904. The results showed that employee’s engagement had a substantial influence on job satisfaction (Adj. R2 = 0.342, p=0.000). Result indicated that employee’s engagement had an independent effect on job satisfaction among library staff across the public tertiary institutions in Ogun and Oyo States, Nigeria. We recommend that management provide flexible working conditions for staff to enhance their job satisfaction.